Spectrophotometric determination of iron and boron in soil extracts using a multi-syringe flow injection system - Gomes, D. M. C. (2010)
In the last decade, significant advances in flow analysis have been reported, namely the extensive use of computer-controlled devices to enhance the autonomy and performance of analysers. In the present work, computer-controlled multi-syringe flow injection systems are proposed to perform the spectrophotometric determination of available iron and boron in soil extracts. The methodologies were based on the formation of ferroin complex (determination of iron) and azomethine-H reaction (determination of boron). Both determinations were performed in manifolds with similar configurations by changing the reagents present in the different syringes. In the determination of iron, elimination of Schlieren effect in the detection system was achieved through the binary sampling approach, where a three-way valve was actuated to intercalate small slugs of sample and reagent, promoting better mixing conditions for solutions with different values of refractive index. In the determination of boron, in-line sample blank measurement was attained by omitting the introduction of reagent through software control, without manifold reconfiguration. Linear calibration curves were established between 0.50 and 10.0 mg Fe l−1 and between 0.20 and 4.0 mgBl−1. No systematic difference was found when soil extracts were analysed by the proposed methodologies and compared to the respective reference procedures.